PTH-003 QIP: improving quality of photodocumentation and lesion reporting in upper gastrointestinal endoscopy. (8th June 2018) - Ahmad, Ahmir; Bottle, Juliet; Laverty, Anthony; Murray, Sam; Ewing, Iain
Abstract : Introduction: The gold standard investigation for upper gastrointestinal (GI) symptoms is oesophago-gastro-duodenoscopy (OGD). The British Society of Gastroenterology (BSG) released a position statement of quality standards in upper gastrointestinal endoscopy in August 2017, including the recommendation to photodocument 8 anatomical sites in the upper GI tract to optimise mucosal inspection and lesion recognition. We aimed to assess and improve the quality of OGD photodocumentation and lesion recognition in line with this recommendation. Methods: 184 OGD reports were audited from three one-week audit cycles. Cycle 1: immediately following guideline release and prior to intervention; cycle 2: immediately following intervention (departmental teaching and poster display of recommended photos in endoscopy procedure rooms); cycle 3: 2 weeks after intervention. Total number of photos taken per procedure, number of anatomical sites photodocumented, and number of lesions detected were recorded. Results: From cycle 1 (pre-intervention) to cycle 2 (post-intervention) the mean number of photos per OGD increased from 5.3 to 8.6 respectively (p=0.095) and mean number of anatomical sites documented increased from 3.8 (47%) to 6.9 (86%) (p<0.001). The mean number of lesions documented per OGD increased from 0.5 to 1.2 (p=0.230). Improvement in practice was sustained through audit cycle 3 (2 weeks after intervention): mean photos 8.5, mean required sites documented 7.4 (92%) and 0.7 diagnoses per OGD. Conclusions: Immediately following release of BSG quality standards in upper GI endoscopy, departmental adherence to recommendations for photodocumentation was poor. A simple intervention of departmental teaching and poster displays resulted in a significant improvement in the quality of photodocumentation and a trend towards improvement in detection of lesions. Improvement in quality was sustained at re-audit.